The waste lands [compact disc, unabridged] - King, Stephen, 1947- (King, Stephen, 1947- Dark tower (Simon & Schuster Audio (Firm)), 2016)
Roland, Susannah, and Eddie continue through Out-World on their quest to find the Dark Tower. However, after an attack by the giant bear, the gunslingers discover one of the six beams that hold the world together and soon discover a path to Mid-World.